Weimar through the Lens of Gender : Prostitution Reform, Woman's Emancipation, and German Democracy, 1919-33 - Roos, Julia (Book collections on Project MUSE., 2010)
Weimar through the Lens of Gender combines the political history of early twentieth-century Germany with analytical perspectives derived from the fields of gender studies and the history of sexuality. The book's argument will be of interest to a broad readership: specialists in the fields of gender studies and the history of sexuality, as well as historians and general readers interested in Weimar and Nazi Germany. --Book Jacket.